Harnessing Educational Technology to Stimulate Critical Thinking among Secondary School Learners for Sustainable Development in Kenya - Njoka, Johannes N.; Githui, Perminus (Machakos University, 2018)
Critical thinking (CT) isan essential life skill that education should seek to equip learners with in order to actualize the attainment of Kenya’s vision 2030 and the sustainable development goals (SDGS). Psychologists and philosophers argue that critical thinking provides individuals with the mental ability to think, inquire and interrogate phenomena in society which eliminates bias and blind acceptance of viewpoints. Individuals who are proficient in critical thinking are able to conduct strategic thinking, creative thinking and engage in appropriate decision making and problem-solving processes. Individuals empowered with these competenciesare characterized with the ability to adjust to diverse demands of their environment. Theoutcome are individualswho arehighly employable, adaptable and inquisitive with a knack to positively influence society with innovations and social reengineering of communities with ideas. There is apparent disconnect between the expected role of education in fostering critical thinking among learners in secondary schools in Kenya.Githui, Njoka and Mwenje (2017) established that the levels of critical thinkingamong secondary school learners in Nairobi and Nyeri Countieswas disturbinglyvery low.The scenario implies that students’ mental abilities hardly perform beyond mere memorization of facts and information. Learners critically lack the abilities to synthesize, analyze and evaluate information. Such students graduate from school deficient in the life skills necessary for effective living, work performance and inability to engage in activities of daily living in society. Unfortunately, educators in majority oflearning institutions in Kenyalack an understanding of howeducational technologycan be harnessed to stimulatecritical thinking skills during teaching and learning processes. This is despite the fact that critical thinking can be infused in pedagogyacross all disciplines without occasioning expensive curriculum reviews. Thisstudyseeks to provideinsights and informationto educators and policy makers on how educational technology can be harnessed to stimulate critical thinking among learners during the teaching and learning process for sustainable development in Kenya.Objectives: The study was guided by the following objectives, which were to;discuss how to harness instructional resources to stimulate critical thinking during the teaching and learning process among learners for sustainable development in Kenya; assess how instructional techniques can be used to promote critical thinking among learners in secondary schools in Kenya and evaluate how assessment techniques can be used in developing critical thinking among learners in secondary schools for sustainable development in Kenya.Methodology:The study adopted the Social Cognitive Theory (SCT) propounded by Albert Bandura as its theoretical framework. The study relied on library review of secondary data and published reports regarding how to harness educational technology to stimulate critical thinking among secondary school learners in Kenya.
Keywords: Critical and creative thinking